ON THE RELATION OF STROKE AND AIR POLLUTION WITH PARTICULATE MATTER. PREVENTION ACTIONS - A. F. Kolpakova (Кардиоваскулярная терапия и профилактика)
The article focuses  on the  contemporary  view on the  relation of air pollution by particulate matter (PM) with morbidity and mortality from the brain stroke. The results of studies are reviewed, on the longand shortterm influence of PM pollution on cardiovascular system depending  on their size, origin, chemistry,  concentration  in the air, as  the ways for stroke prevention.